2017
DOI: 10.1089/end.2017.0078
|View full text |Cite
|
Sign up to set email alerts
|

Non-Angled Intercostal Percutaneous Access Under Full Expiration: Safety Is Not an Issue Anymore

Abstract: Compared to subcostal access, intercostal approach under full expiration is a safe technique that provides optimal approach to the intrarenal collecting system and allows less angulation, less bleeding, and yields higher stone clearance with minimal complications. When performed by a well-trained urologist, intercostal access should be advocated in PCNL to obtain a direct non-angled access to the tip of the desired posterior calix.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…In their article, Ajib , Matta, Zougheib, &Jabbour (2017)demonstrated that intercostal approach under full expiration is in fact safe and allows better access to the intrarenal collecting system with minimal complications. 11 Although no significant difference was observed in terms of overall complications, morbidly obese patients had the highest percentage of > Class II complications (14.29%). This was also shown in the CROES study of the influence of BMI on outcome where there was a higher rate of major complications in super obese, but overall there was no difference.…”
Section: Discussionmentioning
confidence: 80%
“…In their article, Ajib , Matta, Zougheib, &Jabbour (2017)demonstrated that intercostal approach under full expiration is in fact safe and allows better access to the intrarenal collecting system with minimal complications. 11 Although no significant difference was observed in terms of overall complications, morbidly obese patients had the highest percentage of > Class II complications (14.29%). This was also shown in the CROES study of the influence of BMI on outcome where there was a higher rate of major complications in super obese, but overall there was no difference.…”
Section: Discussionmentioning
confidence: 80%
“…Specifically, when provision of access is planned prior to lithotripsy, superior calyceal access is indicated for staghorn calculi, large upper caliceal calculi, calculi associated with ureteropelvic junction (UPJ) pathology, and large upper-ureteral calculi. 23 In these scenarios, upper pole access may necessitate an intercostal approach. An understanding of thoracic anatomy is crucial to minimize complications associated with transpleural access, which include pneumothorax, pleural effusion, urothorax, and intercostal arterial injury.…”
Section: Intercostal Accessmentioning
confidence: 99%
“…24 By accessing above the lateral half of the 12th rib during expiration, injury to the pleura can be minimized. 23 Access above the 11th rib significantly increases the risk of pleural injury, 25 and is therefore avoided in some institutions. 24…”
Section: Intercostal Accessmentioning
confidence: 99%
See 1 more Smart Citation